Optimization of HBsAg retesting process: an improvement in laboratory management system based on health economics - Jingrou Chen; Yang Wang; Lejian Dong; Huimin Fang; Xiaoyu Zhu; Hongxu Xu (Annals of Clinical Biochemistry: International Journal of Laboratory Medicine, 2026)
Objective: To optimize the retesting process for hepatitis B screening, reduce false positives in samples with weak positive signals, and improve the laboratory management system, ensuring no missed cases and eliminating resource waste. Methods: 131 HBsAg-positive samples with initial signal to cut-off (S/CO) values ranging from 0.05 to 10 were divided into 5 intervals. After high-speed centrifugation, the samples were retested for HBsAg, and the initial and retest results were compared. By evaluating the repeatability and accuracy of the HBsAg results in different intervals, the "gray zone" of the HBsAg screening test was identified, and a laboratory optimization process plan was established. The new plan was piloted in parallel with the old plan to assess the reliability of the new plan. Results: In the interval of initial cutoff (S/CO) values [0.05∼0.2], the difference rate between the initial test group and retest group was the highest (40%), and there was a significant difference in the qualitative results (p